Frequency of non-single canals in mandibular premolars and correlations with other anatomical variants: an in vivo cone beam computed tomography study - Young-Eun Jang (BMC Oral Health, 2019)
Abstract Background A knowledge regarding anatomical variants is important to achieve success in endodontic treatment. Root canal treatment of mandibular first premolars (PM1 s) is challenging due to the existence of numerous variations in canal configurations, including a C-shaped variant. We aim to determine the frequency and morphologic characteristics of non-single canals of mandibular first (PM1 s) and second (PM2 s) premolars in a Korean population using cone beam computed tomography (CBCT) and to evaluate correlations between non-single canals of PM1 s and other anatomical variants, such as distolingual roots (DLRs) in mandibular first molars (M1 s) and C-shaped canals in mandibular second molars (M2 s). Methods A total of 971 PM1 s and 997 PM2 s from 500 patients were examined in vivo by CBCT. Root canal configurations and C-shaped canals were determined in accordance with the Vertucci classification and Fan classification, respectively. The correlation between non-single canals in PM1 s and DLRs in M1 s was evaluated using logistic regression analysis. Results PM2 s typically had one root (99.89%) with one canal (98.4%). Among PM1 s with non-single canals (21.2%), Vertucci type V (10.9%) and C-shaped (3.7%) canals were prevalent. Among C-shaped PM1 canals, the majority were Vertucci type V (77.8%); a C-shaped configuration (C2) was predominant mostly at the middle and/or apical third of the root. After adjusting for other variables (i.e., sex, age, and side), C-shaped canals in PM1 s was significantly correlated with the presence of DLRs in M1 s (odds ratio = 2.616; 95% confidence interval, 1.257–5.443; p = 0.010). Conclusions The presence of C-shaped PM1 canals was positively related to the presence of DLRs in M1 s. Although C-shaped canals in PM1 s are difficult to distinguish, this finding could aid clinicians in predicting C-shaped canal configurations in PM1 s of patients who exhibit DLRs in M1 s.